Grenadine - Wechsler, Neil, 1974- (Yale drama series., 2009)
"Neil Wechsler's Grenadine has been chosen as the second winner of the Yale Drama Series. The play was selected by Pulitzer Prize-winning playwright and contest judge Edward Albee. Grenadine is the fantastical story of a man's quest for love in the company of three devoted friends. Albee writes, "I found it highly original ... The questions the play asks and the answers it proposes are provocative; the play stretched my mind.""--Jacket